2012
DOI: 10.1249/mss.0b013e318244a321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motor Control Training on Muscle Size and Football Games Missed from Injury

Abstract: The motor control program delivered to elite footballers was effective, with demonstrated changes in the size and control of the targeted muscles. In this study, footballers who received the intervention early in the season missed fewer games because of injury than those who received it late in the playing season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 35 publications
2
63
1
3
Order By: Relevance
“…A recent study reported that of 46 players in an elite squad, 13 reported current low back pain, 14 had a history of low back pain, and 19 did not have low back pain. 19 In the current investigation, players with recent low back pain showed increased odds of a lower limb injury in the preseason. While not many players miss games during the season due to low back pain, the presence of low back pain is likely to affect performance and how players move.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…A recent study reported that of 46 players in an elite squad, 13 reported current low back pain, 14 had a history of low back pain, and 19 did not have low back pain. 19 In the current investigation, players with recent low back pain showed increased odds of a lower limb injury in the preseason. While not many players miss games during the season due to low back pain, the presence of low back pain is likely to affect performance and how players move.…”
Section: Discussionmentioning
confidence: 59%
“…While the results support implementation of programs that effectively rehabilitate the multifidus muscle, 19 the level of specificity obtained for the playing season may need to be increased before the model is used as a screening tool to select players who need not be treated. However, the high level of specificity and moderately high level of sensitivity for the preseason model indicate that such interventions could target players with relatively smaller multifidus muscles (adjusted for other factors in the model).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A similar MCT approach has been used on Earth for people with acute LBP, chronic LBP, elite cricketers and elite Australian Football League players (Hides et al, 1996;Hides et al, 2008;Hides, Stanton, Mendis, Gildea, & Sexton, 2012). The programme has been shown to decrease LBP, was commensurate with decreased games missed due to injury and was predictive of injury Hides, Mendis, et al, 2016;Hides et al, 2014).…”
Section: Lessons From the Patient With Low Back Pain And Elite Athletesmentioning
confidence: 99%